2012
DOI: 10.1002/cjoc.201180457
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Pt Catalyst Modified by Sn Electrodeposition for Electrochemical Oxidation of Formaldehyde

Abstract: A nanoporous Pt particles-modified Ti (nanoPt/Ti) electrode was prepared through a simple hydrothermal method using aqueous H 2 PtCl 6 as a precursor and formaldehyde as a reduction agent. The nanoPt/Ti electrode was then modified with limited amounts of tin particles generated by cyclic potential scans in the range of formaldehyde oxidation can be illustrated by a so-called bifunctional mechanism which is involved in the oxidation of poisoning adsorbed CO species via the surface reaction with OH adsorbed on n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…[47] The deconvolution of Sn 3d is shown in Figure 3c, which gives quartet distinct absorption spectra at binding energies of 484.9, These results reveal that there is a thin Sn film on the SnO 2 (abbreviated herein as Sn@SnO 2 ) in the Pd/SnO 2 /MOFDC matrix structure because the MOFDC further reduces some of the SnO 2 to Sn. The thin Sn film exhibits the oxophilic, [32] while the SnO 2 has spill-over effects to enhance the alkaline HOR. [34] Figure 3d-3 f displays the high-resolution C 1s, O 1s and N 1s core-level XPS spectra of the Pd/SnO 2 /MOFDC, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[47] The deconvolution of Sn 3d is shown in Figure 3c, which gives quartet distinct absorption spectra at binding energies of 484.9, These results reveal that there is a thin Sn film on the SnO 2 (abbreviated herein as Sn@SnO 2 ) in the Pd/SnO 2 /MOFDC matrix structure because the MOFDC further reduces some of the SnO 2 to Sn. The thin Sn film exhibits the oxophilic, [32] while the SnO 2 has spill-over effects to enhance the alkaline HOR. [34] Figure 3d-3 f displays the high-resolution C 1s, O 1s and N 1s core-level XPS spectra of the Pd/SnO 2 /MOFDC, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…(2)], and the addition of M to the Pd in the alloy/composite reduces the HBE beneficial for facile HOR, and ii) chemisorption and promotional donation of OH À by the M in the supporting electrolyte [Eq. (3), Volmer step, RDS], which could be ascribed to either oxophilic [32,33] or spillover process, [34,35] or both for facile alkaline HOR. Some workers have shown that the presence of co-catalysts in Pd (such as CeO 2 , [36,37] Ir [38] and Mo [39] ) improves alkaline HOR kinetics and stability.…”
Section: Introductionmentioning
confidence: 99%
“…These advancements include the development of novel synthesis methods, understanding the nanoscale interaction between the two metals, and exploring various combinations of metals. Currently reported bimetallic nanocatalysts for electrochemical detection of formaldehyde include Pt-Ru [ 109 ], Pd–Pt [ 110 , 115 , 156 ], Pd-Au [ 111 ], Ag-Pd [ 112 ], Sn-Pt [ 113 ], Cu-Pd [ 114 , 116 ], Ni-Pd [ 117 ], Pt–Ag [ 118 ], and Cr-Pd [ 119 ]. Due to Pd’s high catalytic activity and low susceptibility to poisoning during anodic oxidation, it is commonly used in alloy materials.…”
Section: Electrochemical Sensors For Formaldehydementioning
confidence: 99%